Prosumer integration into the Brazilian energy sector: An overview of innovative business models and regulatory challenges. (February 2022) - Botelho, D.F.; de Oliveira, L.W.; Dias, B.H.; Soares, T.A.; Moraes, C.A.
Abstract: Considering the Brazilian energy policy's future, the perspective of a more decentralized energy system must be accounted for in the face of technological, business, and energy matrix changes. Therefore, the prosumer's figure combined with new Business Models (BM) brings opportunities and challenges for the sector. This paper aims to solidify knowledge, identify and understand the main regulatory barriers and enablers for the development of prosumers and prosumer-driven BMs in the Brazilian energy market. A comprehensive review of existing regulations provides a starting point for improving the relevant legal frameworks for prosumers' aggregation. Then, an analysis of innovative BMs in the Brazilian regulatory framework is carried out, seeking to guide the decisions for the country to develop its political and regulatory environment in the future. The paper concludes with policy recommendations to promote prosumers aggregation in the Brazilian energy sector. We conclude that the main barriers to prosumers' integration are of regulatory and technological nature, and the exploration of innovative BMs is crucial for the sector development. Redefining the role and responsibilities of utilities is a key factor, together with exploring collective self-consumption. Highlights: Innovative business models are essential for the prosumers' integration. Key barriers for prosumers are of regulatory and technology nature. Five policy recommendations are proposed to overcome existing barriers.